2022
DOI: 10.1002/jcla.24351
|View full text |Cite
|
Sign up to set email alerts
|

Association between red blood cell distribution width‐to‐albumin ratio and diabetic retinopathy

Abstract: Diabetes mellitus (DM) has shown a trend of reaching pandemic levels in the world. [1][2][3] It has rapidly become a global health problem.Diabetic retinopathy (DR) is the most common microvascular complication of type 2 diabetes mellitus (T2D) and the most frequent. 4 DR is one of the major eye diseases causing blindness in people aged 50 years and above. 5 Its basic pathological changes are destruction of blood retinal barrier (BRB) and the formation of retinal neovascularization. 6 Studies 7 on the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Experimental evidence has shown that albumin has antioxidant activity, and plays a protective role by thinning the blood and reducing oxidative stress ( 35 37 ). Several studies have shown that serum albumin level is associated with the outcomes of various diseases including cardio-cerebrovascular diseases, mainly due to malnutrition and inflammation ( 15 , 33 , 38 40 ). Moreover, low serum albumin concentration has been reported to be associated with adverse clinical outcomes of ischemic heart disease ( 41 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence has shown that albumin has antioxidant activity, and plays a protective role by thinning the blood and reducing oxidative stress ( 35 37 ). Several studies have shown that serum albumin level is associated with the outcomes of various diseases including cardio-cerebrovascular diseases, mainly due to malnutrition and inflammation ( 15 , 33 , 38 40 ). Moreover, low serum albumin concentration has been reported to be associated with adverse clinical outcomes of ischemic heart disease ( 41 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a low serum albumin level is strongly negatively correlated with the risk of death from cardiovascular diseases ( 12 ). Recent studies have shown that the ratio of RDW to albumin (RA) is associated with the prognosis of a variety of diseases, including aortic aneurysm, diabetic retinopathy, and shock ( 13 15 ). However, it is unknown whether combining RDW with albumin can more effectively predict the prognosis of patients after PCI.…”
Section: Introductionmentioning
confidence: 99%
“…RDW to albumin ratio (RAR) is a novel and simple biomarker of inflammation. Previous studies have demonstrated that RAR is associated with the prognosis of diabetic ketoacidosis (20), diabetic retinopathy (21), and cancer (22). Previous studies have demonstrated the effectiveness of RAR in predicting the prognosis of diseases such as diabetic ketoacidosis, diabetic retinopathy, and cancer.…”
Section: Introductionmentioning
confidence: 99%
“… 4 In addition, albumin has been shown to be an inflammation marker. 13 , 30 In the studies of Chen and Takegawa et al, the albumin levels were emphasized to be a prognostic factor in patients with pneumonia or sepsis. 16 , 31 In many recent studies, low albumin levels on admission were proposed to be associated with all the other negative outcomes in addition to mortality in patients with severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…33 Therefore, RAR alone can reflect inflammatory states more accurately than either marker. 13,15,30 In the study of Yoo et al, conducted with patients with ARDS, the RAR levels were associated with 60-day mortality (hazard ratio 1.134, p = 0.003). The authors also reported that the calculated AUC value for RAR was higher than that for RDW alone (0.681, 0.576, respectively, p= 0.002).…”
mentioning
confidence: 99%